Правовий режим селянських лісів на території України за часів Російської імперії (XVIII – початок ХХ століття) - Смолярчук, Р.; Smoliarchuk, R. (Східноєвропейський національний університет імені Лесі Українки, 2017)
Стаття присвячена дослідженню розвитку правового режиму селянських лісів у дореволюційний період. Досліджено умови становлення селянських лісів як окремої категорії лісів державної власності, та формування їх в якості громадської власності громад. Проведено періодизацію розвитку правового режиму селянських лісів в Російській імперії. The article investigates the legal regime of the peasant forests in the prerevolutionary period. The author analyzes the main types of restrictions on the use of public forests in the period of the feudal-serf system formation on the territory of Ukraine, which manifested themselves in the formation of private ownership, satisfying the needs of the state, introducing quantitative restrictions and setting fees for the use of forest resources. The emphasis is laid on the conditions of the emergence of peasants-owned forests as a distinct form of the state-owned forests. The study reveals peculiarities of the formation of peasants’ ownership of forests as a form of public property, in particular, the reasons for the emergence of such ownership of forests in the rural community and identifies certain legislative restrictions on forest use by peasants in the context of their acquisition of such kind of property. The author suggests general periodization concerning the development of the legal status of peasant forests and reveals the peculiarities of forest management in peasant-owned forests of Russian Empire.
Legal Regime of Peasant Forests on the Territory of Ukraine in the Times of Russian Empire (XVIII – Beginning of XX century)
Keywords: ліс; лісокористування; селянські ліси; правовий режим селянських лісів; лісове законодавство Російської імперії; forest; forest use; peasant forests; legal status of peasant forests; forest legislation in Russian Empire